Diabetic osteoarthropathy: modern methods of therapy - Irina N. Ul'yanova; Alla Y. Tokmakova; Марианна V. Yaroslavtseva; Alexander V. Ilyin; Gagik R. Galstyan (Сахарный диабет, 2010)
This paper is focused on the main aspects of pathogenesis of diabetic osteoarthropathy (DOAP) underlain by motor and sensory neuropathies, injuries(including microfractures and joint disintegration), and inflammation accompanied by enhanced cytokine expression. The role of osteopenia andbone resorption-formation decoupling at different stages of DOAP is discussed. Modern methods of DOAP treatment are considered with special referenceto immobilization, drug therapy, surgical and orthopedic care